PENGARUH TERPAAN MEDIA SOSIAL PADA AKUN TIKTOK JOGJAFOODHUNTER TERHADAP MINAT BELI KONSUMEN - Hidayati, Ulfah (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2022)
TikTok became a mobile application that was ranked first among other more popular applications such as Facebook, WhatsApp, and Instagram in 2020. Not a few culinary entrepreneurs also use advertising services through the food blogger TikTok. One of the TikTok food blogger accounts in Yogyakarta with the most followers is the Jogjafoodhunter account. This study aims to determine the effect of TikTok Jogjafoodhunter account exposure on consumer buying interest. This study uses a quantitative approach with a survey method. The population of this study is the followers of the TikTok Jogjafoodhunter account, totaling 630,100 people. The sample is 100 using simple random sampling method. Data collection techniques using a questionnaire. All tests were carried out with the help SPSS 21 software. The results showed that there was a positive influence between social media exposure on the Jogjafoodhunter TikTok account (X) on consumer buying interest (Y) which was indicated by a positive correlation value (R) of 0.745 and the value of the coefficient of determination (R square) X against Y is 0.554. This shows that the contribution of social media exposure to the TikTok Jogjafoodhunter account on consumer buying interest is 55.4% while the remaining 44.6% is determined by other variables not examined. In addition, the existence of a positive influence between variable X and variable Y can be proven based on the value of Sig. 0.000 <0.05 so that it can be concluded that Ha in this study received. (2) the stimulus or content on the TikTok Jogjafoodhunter account will make consumers or followers of the account respond to the content uploaded by the account. The response or reaction that was researched and obtained in this study was the emergence of consumer buying interest in the exposure of the Jogjafoodhunter TikTok account.